EXPLORING THE IMPACT OF SPIRITUAL AND EMOTIONAL INTELLIGENCE ON TRANSACTIONAL AND TRANSFORMATIONAL LEADERSHIP - Keny, Vincent (Digital Repository of Theses, 2023)
Introduction: The global economy has become more competitive and complicated, and a significant number of people believe they still lack the appropriate skills for their jobs. These days, soft skills, such as emotional and spiritual intelligence, are vital in the workplace. The “spiritually intellectual manager” bases their performance with support, focusing and understanding inner strengths of the staff. On the other hand, “emotionally intellectual manager” bases top performance with awareness and empathy towards the needs of employees. Objective: The purpose of this research is to investigate the impact of Spiritual and Emotional Intelligence on the capacity of people managers to strike a balance between transactional and transformational leadership. The research is also concerned with identifying the key elements of Spiritual and Emotional Quotient exhibited by people managers in the form of transactional and transformational leadership behaviours, identifying the continuous practises vi that trigger Spiritual and Emotional Intelligence, and determining how Spiritual and Emotional Intelligence can lead to increased productivity in business organisations. Methodology: In this study, quantitative research was done using the Multifactor Leadership Questionnaire (MLQ-6S), a condensed version of the original developed by Avolio and Bass. There are 3 main MLQ variants: Spiritual Quotient, Emotional Quotient and Transactional and Transformational Leadership. Each leader was required to take one of these surveys in order to assess their own leadership skills. On the MLQ-6S Form, each of the twenty-one primarily leadership-related items was measured using a Likert scale. In an effort to examine the hypothesis, One-Way ANOVA tests were conducted using the SPSS programme. Result: Spiritual and Emotional Intelligence were discovered to have a positive impact on the performance of people managers in a business organization. It was also revealed that spiritual and emotional intelligence had a good effect on leadership abilities. In order to maintain a healthy balance between transformational and transactional leadership in organizations, SQ and EQ must be integrated. Conclusion: This study discovered an emotional and spiritual intelligence framework. According to research, leaders who are empathetic, empathic, and supportive are more likely to develop strong teams. This study backs up the notion that emotional and spiritual intelligence are related. Additionally spiritual intelligence may be created by emotionally intelligent leaders and spiritually and emotionally knowledgeable leaders have the potential to inspire their followers.